A New History of Identity - Armstrong, D. author. aut Link
X, 213 p.
Keywords: Medical texts provide a powerful means of accessing contemporary perceptions of illness and through them assumptions about the nature of the body and identity. By mapping these perceptions, from their nineteenth-century focus on illness located in a biological body through to their 'discovery' of the psycho-social patient of the late twentieth century, a history of identity, both physical and psychological, is revealed.